Framing Juvenile Delinquents As The Pathological Individual - Ali, Kamsiah (Institute of East Asian Studies, Universiti Malaysia Sarawak, 2013)
The common conceptions of troubled youth often focus on the nature of youth violence or crime. As stated by Bernard Schissel, "although habitual and potentially dangerous offenders are the small minority, only their activities and characteristics seem to inform the moral panic debates” (Schissel 2006: p. 11). A lot of what is known about youth is driven by the media; the form of knowledge can influence the public discourse about youths (Tanner, 2001; Schissel, 1997). This paper analyses the way in which the category of 'youth' has been constructed through moral panics which frame youth as the pathological individual or as 'evil people' and blaming them for the social problems and fear in the society. The moral panics create social consequences for youth because the panic can influence how we understand youth and their problem. The panic surrounding youth as the representations of crime influenced both the way trouble youth were understood either as crime or pre-criminal and what was understood to be the appropriate response to their problem.